A Development of a Word Guessing Game to Enhance Critical Thinking Skills and Learning Motivation for Junior High School Students - Watchara Yenprem (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2022)
The objectives of this study were; 1) to develop the “Word Guessing” game which can improve critical thinking skills and learning motivation of the junior high students, and 2) to evaluate the learning satisfaction of the junior high students towards the “Word Guessing” game in terms of critical thinking skills and learning motivation improvement. The research samples were 50 junior high school students of Watphraphutthabath Khaolukchang School (Phiphitphatthananukroh), Phetchaburi Province, Thailand. The sample group was selected by purposive sampling. A questionnaire with the IOC of 0.90 was used for data collection. From the study, it was found that the “Word Guessing” game presented with PowerPoint software consists of 8 questions with 5 clues that require the students playing in teamwork system to think critically in order to give the correct answers under the set of rules and using the game itself motivates them to like learning. The students had a positive attitude in critical thinking skills and learning motivation improvement at a high level ( =3.94 - 4.62).